Low-cost high-strength flame-retardant magnesium alloy profile and preparation method thereof
By adding Sn, Mn, Zn, Sr and Si elements to the magnesium alloy and using surface treatment of modified nanomagnesium hydroxide and nanosilicon dioxide, the problem of insufficient flame retardant performance of magnesium alloy is solved, and high strength is achieved. Low-cost flame-retardant magnesium alloy, suitable for light rail transit and other fields.
Patent Information
- Application Number
- CN202411247667.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-17
AI Technical Summary
The flame retardant performance of existing magnesium alloys is insufficient, especially in the field of light rail transit, which brings safety hazards. The cost of commonly used rare earth elements is high, which limits the large-scale application of flame retardant magnesium alloys.
By adding appropriate amounts of Sn, Mn, Zn, Sr and Si elements to the Mg-Al-Ca alloy, and optimizing the alloy structure through high-temperature treatment, combining the surface treatment of modified nanomagnesium hydroxide and nanosilicon dioxide to form a dense micro-nanolayers to improve flame retardant performance.
It has achieved a high-strength flame-retardant magnesium alloy with low cost and a ignition point of 1500℃, with good mechanical properties and market application prospects, and no need to add rare earth elements.
Smart Images

Figure CN119144882A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of magnesium alloy materials, and in particular relates to a low-cost, high-strength, flame-retardant magnesium alloy profile and a preparation method thereof. Background Art
[0002] Pure magnesium element materials have low strength and are difficult to be used directly as structural materials. Therefore, appropriate alloying elements are selected in engineering to make magnesium alloys to meet various engineering needs. Compared with other structural materials, magnesium alloys have many advantages such as low density, high specific strength and specific stiffness, high dimensional stability, good anti-electromagnetic interference and electromagnetic shielding, environmental protection and pollution-free, good casting performance, and good cutting processability. They are widely used in various fields such as automotive parts, aerospace structural parts, and 3C communication electronic devices. Taking the automotive industry as an example, the application of magnesium alloys in automobiles has achieved a breakthrough from 0 to 1, and gradually penetrated from small parts to large parts. According to statistics, the consumption of magnesium alloys in the automotive industry will reach 100,000 tons in 2022, and the average single vehicle will use more than 3.5 kg of magnesium alloys; it is expected that the total consumption will reach 450,000 tons in 2030, and the average single vehicle will use more than 14.5 kg. With the further growth of demand and the advancement of industrial technology, magnesium alloy materials will have unprecedented development opportunities in various high-end equipment fields. However, development opportunities always coexist with difficulties and challenges. Since magnesium alloy is a very active metal material, it must have good flame retardancy in practical applications. Especially in the field of light rail transportation, magnesium alloy with low ignition point will bring great safety hazards.
[0003] Currently, the common commercial magnesium alloy brands have low ignition points and low practical application value in rail transit vehicle body profiles. In the prior art, a certain amount of other alloying elements are usually added to give the magnesium alloy some high performance while also improving the ignition point of the magnesium alloy. At present, the flame-retardant magnesium alloys reported at home and abroad basically have various Re-series rare earth elements added, and the cost of rare earth elements is relatively high, which seriously limits the large-scale application of flame-retardant magnesium alloys. Mg‑Al‑Ca alloys have the advantages of low cost, high strength, and high ignition point. The ignition point of the alloy in this system is mainly determined by the Ca content, but as the Ca content increases, the plasticity of the alloy will become very poor, which is not conducive to practical application. Therefore, how to prepare a low-cost and high-strength flame-retardant magnesium alloy has become a technical problem that needs to be solved urgently. Summary of the invention
[0004] The purpose of the present invention is to provide a low-cost and high-strength flame-retardant magnesium alloy profile and a preparation method thereof. The prepared flame-retardant magnesium alloy not only has good comprehensive mechanical properties, but also has the advantages of high ignition point and low cost, and has good market application prospects.
[0005] In order to achieve the above technical objectives, the technical solution adopted by the present invention is: A low-cost high-strength flame-retardant magnesium alloy profile is made of the following raw materials in weight percentage: Al 10.2-11.0%, Sn 0.9-1.1%, Ca 0.75-1.3%, Zn 0.4-0.8%, Mn 0.1-0.5%, Si 0.2-0.4%, Sr 0.1-0.3%, the balance Mg and inevitable impurities.
[0006] A method for preparing the above-mentioned low-cost, high-strength, flame-retardant magnesium alloy profile comprises the following steps: 1) Prepare raw materials: weigh the raw materials according to the mass percentage of each raw material in the magnesium alloy, wherein magnesium, aluminum, zinc, and tin are added in the form of pure magnesium ingots, aluminum ingots, zinc ingots, and tin ingots, calcium, strontium, and silicon are added in the form of magnesium-calcium alloy, magnesium-strontium alloy, and magnesium-silicon alloy, and manganese is manganese chloride; 2) Melting: First, the magnesium ingot is preheated, and the preheated magnesium ingot is placed in the furnace body for melting under the protection of mixed gas A. After the melting is complete, the preheated aluminum ingot, zinc ingot, tin ingot, magnesium calcium alloy, magnesium strontium alloy, magnesium silicon alloy and No. 2 flux, and manganese chloride are added thereto and continue to be mixed and smelted at 710-740°C under the protection of mixed gas B. After all are melted, a refining agent is added and refined for 10-15 minutes, and then degassing, slag removal and heat preservation treatment are carried out in sequence to obtain an alloy melt, and a covering agent is added. The melt is left to stand for 15-20 minutes, and the semi-continuous casting billet is obtained when the temperature reaches 670-690°C; 3) Homogenization treatment: homogenize the semi-continuous casting billet, then cool it to room temperature and turn the outer surface to the appropriate size; 4) Forming processing: The homogenized billet is preheated before extrusion, extruded and aged to obtain a flame-retardant magnesium alloy profile; 5) Surface treatment: The flame retardant magnesium alloy profile obtained in step 4) is immersed in anhydrous ethanol for ultrasonic cleaning for 3-5 minutes, taken out and air-dried, and then immersed in a 3% acetic acid solution for 10-15 seconds, then rinsed with clean water until neutral, and then immersed in a surface treatment agent for 30 minutes, taken out and naturally dried to obtain the final product.
[0007] Preferably, the mixed gas A is composed of air, carbon dioxide and sulfur hexafluoride in a volume ratio of 50:50:3; and the mixed gas B is composed of carbon dioxide and sulfur hexafluoride in a volume ratio of 97:3.
[0008] Preferably, the homogenization treatment method is: using gradient setting temperature homogenization treatment, specifically, setting the temperature to 100°C and keeping warm for 30 minutes; setting the temperature to 200°C and keeping warm for 20 minutes; setting the temperature to 300°C and keeping warm for 20 minutes; setting the temperature to 390°C and keeping warm for 21 hours.
[0009] Preferably, the aging treatment is carried out at a temperature of 177±6°C, for 6 hours, and at a heating rate of 5°C / min.
[0010] Preferably, the surface treatment agent is composed of modified nano magnesium hydroxide slurry and silica sol in a volume ratio of 1:1; the mass fraction of the modified nano magnesium hydroxide slurry is 10%.
[0011] Preferably, the modified magnesium hydroxide is prepared by the following method: a) preparing anhydrous ethanol and deionized water in a volume ratio of 9:1 to prepare an alcohol-water solvent, mixing N-phenyl-γ-aminopropyltrimethoxysilane coupling agent and the alcohol-water solvent in a volume ratio of 100:1, stirring and hydrolyzing with magnetic stirring for 1 hour to obtain a silane hydrolyzate; b) Nano magnesium hydroxide was weighed and prepared into a nano magnesium hydroxide slurry with a mass fraction of 10%. After ultrasonic dispersion treatment for 15 minutes, the slurry was heated to 90° C., and then the silane hydrolyzate obtained in step a) was slowly dripped into it under magnetic stirring. After the dripping was completed, the system was kept reacting for 45 minutes, and then the obtained white slurry was filtered to obtain a white filter cake, and then the filter cake was washed three times with deionized water and anhydrous ethanol respectively to obtain modified nano magnesium hydroxide.
[0012] Preferably, the volume ratio of the nano-magnesium hydroxide slurry to the silane hydrolyzate is 10:1; the nano-magnesium hydroxide is flaky nano-magnesium hydroxide, and its average particle size D50 is 500 nm.
[0013] Preferably, the silica sol contains 25% nano-silicon dioxide, has a particle size of 50-80 nm, and has a pH of 8-8.5.
[0014] Unless otherwise specified, the reagents and raw materials used in the present invention are all purchased from the market. Among them, nano magnesium hydroxide was purchased from a chemical company in Jinan, which is flaky nano magnesium hydroxide with an average particle size D50 of 500 nm.
[0015] The present invention adds appropriate amounts of several metal elements such as Sn, Mn, Zn, Sr and a small amount of non-metallic element Si on the basis of Mg-Al-Ca alloy, optimizes and adjusts the ratio of Ca, Sn and Si in the magnesium alloy, forms a better alloy structure through high-temperature treatment at different stages, improves the phenomenon that the alloy plasticity deteriorates due to the addition of Ca content, increases the ignition point of the alloy material, and fundamentally improves the mechanical properties and flame retardant properties of the alloy.
[0016] On the other hand, by further surface treatment of the magnesium alloy, the surface of the magnesium alloy is firstly washed with alcohol and pickled to remove impurities and dirt on the surface of the alloy, and at the same time, the roughness and activity of the alloy surface are improved, and the interaction between the alloy matrix and the surface treatment agent is promoted; since nano-magnesium hydroxide usually has a small particle size, a large specific surface area but poor dispersibility, after its surface is modified by silane grafting, its hydrophobicity is enhanced, its dispersibility on the matrix surface is improved, and its interaction with the matrix is significantly enhanced; the modified nano-magnesium hydroxide has an endothermic effect at high temperature, which can significantly reduce the ignition point of the alloy material, and at the same time, the magnesium oxide and water vapor generated after the thermal decomposition of nano-magnesium hydroxide, magnesium oxide It is a highly fire-resistant substance. These magnesium oxide particles will adhere to the surface of magnesium alloys. Due to the high consistency with the physical and chemical properties of the magnesium alloy matrix, they can form a dense and stable protective layer. At the same time, water vapor can also mix with combustible gases to form a non-flammable mixed gas, thereby preventing the spread of combustible gases. The modified nano-magnesium hydroxide and nano-silicon dioxide can be used together to form a denser and more uniform micro-nano layer on the alloy surface. This micro-nano layer can effectively isolate the spread of heat and combustible gases, thereby improving the flame retardant properties of the alloy. At the same time, due to the filling of a variety of nanoparticles with different structures on the surface of the magnesium alloy, the mechanical properties of the alloy material are also improved to a certain extent.
[0017] The beneficial effects of the present invention are: (1) The flame-retardant magnesium alloy prepared by the present invention does not add any rare earth elements, has lower cost, and its ignition point can reach 1500°C, has good flame retardant properties, and has broad market application prospects.
[0018] (2) The flame-retardant magnesium alloy prepared by the present invention has excellent room temperature mechanical properties. At room temperature, the tensile strength is above 360 MPa, the room temperature yield strength is above 310 MPa, the elongation is above 17%, and the mechanical properties are excellent. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The surface morphology SEM of the sample prepared in Example 3, wherein (a) is the surface electron microscope image of the flame-retardant magnesium alloy, (b) is the partial enlarged image of (a), and (c) is the partial enlarged image of (b); Figure 2 This is a diagram showing the combustion test results of the sample prepared in the present invention at a high temperature of 1500°C. DETAILED DESCRIPTION
[0020] The technical solution of the present invention is further described below in conjunction with specific embodiments, but is not limited thereto.
[0021] Example 1 A low-cost high-strength flame-retardant magnesium alloy profile is made of the following raw materials in weight percentage: Al 10.2%, Sn 0.9%, Ca 0.75%, Zn 0.4%, Mn 0.1%, Si 0.2%, Sr 0.1%, the balance Mg and inevitable impurities.
[0022] A method for preparing the above-mentioned low-cost, high-strength, flame-retardant magnesium alloy profile comprises the following steps: 1) Prepare raw materials: weigh the raw materials according to the mass percentage of each raw material in the magnesium alloy, wherein magnesium, aluminum, zinc, and tin are added in the form of pure magnesium ingots, aluminum ingots, zinc ingots, and tin ingots, calcium, strontium, and silicon are added in the form of magnesium-calcium alloy, magnesium-strontium alloy, and magnesium-silicon alloy, and manganese is manganese chloride; 2) Melting: First, the magnesium ingot is preheated, and the preheated magnesium ingot is placed in the furnace body for melting under the protection of mixed gas A. After the melting is complete, the preheated aluminum ingot, zinc ingot, tin ingot, magnesium calcium alloy, magnesium strontium alloy, magnesium silicon alloy and No. 2 flux, and manganese chloride are added thereto and continue to be mixed and smelted at 710-740°C under the protection of mixed gas B. After all are melted, a refining agent is added and refined for 10-15 minutes, and then degassing, slag removal and heat preservation treatment are carried out in sequence to obtain an alloy melt, and a covering agent is added. The melt is left to stand for 15-20 minutes, and the semi-continuous casting billet is obtained when the temperature reaches 670-690°C; 3) Homogenization treatment: homogenize the semi-continuous casting billet, then cool it to room temperature and turn the outer surface to the appropriate size; 4) Forming processing: The homogenized billet is preheated before extrusion, extruded and aged to obtain a flame-retardant magnesium alloy profile; 5) Surface treatment: The flame retardant magnesium alloy profile obtained in step 4) is immersed in anhydrous ethanol for ultrasonic cleaning for 3-5 minutes, taken out and air-dried, and then immersed in a 3% acetic acid solution for 10-15 seconds, then rinsed with clean water until neutral, and then immersed in a surface treatment agent for 30 minutes, taken out and naturally dried to obtain the final product.
[0023] The mixed gas A is composed of air, carbon dioxide and sulfur hexafluoride in a volume ratio of 50:50:3; the mixed gas B is composed of carbon dioxide and sulfur hexafluoride in a volume ratio of 97:3.
[0024] The homogenization treatment method is: using gradient setting temperature homogenization treatment, specifically, setting the temperature to 100°C and keeping warm for 30 minutes; setting the temperature to 200°C and keeping warm for 20 minutes; setting the temperature to 300°C and keeping warm for 20 minutes; setting the temperature to 390°C and keeping warm for 21 hours.
[0025] The aging treatment was performed at a temperature of 177±6°C, for a time of 6 hours, and at a heating rate of 5°C / min.
[0026] The surface treatment agent is composed of modified nano magnesium hydroxide slurry and silica sol in a volume ratio of 1:1; the mass fraction of the modified nano magnesium hydroxide slurry is 10%.
[0027] The modified magnesium hydroxide is prepared by the following method: a) preparing anhydrous ethanol and deionized water in a volume ratio of 9:1 to prepare an alcohol-water solvent, mixing N-phenyl-γ-aminopropyltrimethoxysilane coupling agent and the alcohol-water solvent in a volume ratio of 100:1, stirring and hydrolyzing with magnetic stirring for 1 hour to obtain a silane hydrolyzate; b) Nano magnesium hydroxide was weighed and prepared into a nano magnesium hydroxide slurry with a mass fraction of 10%. After ultrasonic dispersion treatment for 15 minutes, the slurry was heated to 90° C., and then the silane hydrolyzate obtained in step a) was slowly dripped into it under magnetic stirring. After the dripping was completed, the system was kept reacting for 45 minutes, and then the obtained white slurry was filtered to obtain a white filter cake, and then the filter cake was washed three times with deionized water and anhydrous ethanol respectively to obtain modified nano magnesium hydroxide.
[0028] The volume ratio of the nano magnesium hydroxide slurry to the silane hydrolyzate is 10:1; the nano magnesium hydroxide is flaky nano magnesium hydroxide, and its average particle size D50 is 500nm.
[0029] The silica sol has a nano-silicon dioxide content of 25%, a particle size of 50 nm, and a pH of 8.
[0030] Example 2 A low-cost, high-strength, flame-retardant magnesium alloy profile is made of the following raw materials in weight percentage: Al 11.0%, Sn 1.1%, Ca 1.3%, Zn 0.8%, Mn 0.5%, Si 0.4%, Sr 0.3%, and the balance Mg and inevitable impurities.
[0031] A method for preparing the above-mentioned low-cost, high-strength, flame-retardant magnesium alloy profile comprises the following steps: 1) Prepare raw materials: weigh the raw materials according to the mass percentage of each raw material in the magnesium alloy, wherein magnesium, aluminum, zinc, and tin are added in the form of pure magnesium ingots, aluminum ingots, zinc ingots, and tin ingots, calcium, strontium, and silicon are added in the form of magnesium-calcium alloy, magnesium-strontium alloy, and magnesium-silicon alloy, and manganese is manganese chloride; 2) Melting: First, the magnesium ingot is preheated, and the preheated magnesium ingot is placed in the furnace body for melting under the protection of mixed gas A. After the melting is complete, the preheated aluminum ingot, zinc ingot, tin ingot, magnesium calcium alloy, magnesium strontium alloy, magnesium silicon alloy and No. 2 flux, and manganese chloride are added thereto and continue to be mixed and smelted at 710-740°C under the protection of mixed gas B. After all are melted, a refining agent is added and refined for 10-15 minutes, and then degassing, slag removal and heat preservation treatment are carried out in sequence to obtain an alloy melt, and a covering agent is added. The melt is left to stand for 15-20 minutes, and the semi-continuous casting billet is obtained when the temperature reaches 670-690°C; 3) Homogenization treatment: homogenize the semi-continuous casting billet, then cool it to room temperature and turn the outer surface to the appropriate size; 4) Forming processing: The homogenized billet is preheated before extrusion, extruded and aged to obtain a flame-retardant magnesium alloy profile; 5) Surface treatment: The flame retardant magnesium alloy profile obtained in step 4) is immersed in anhydrous ethanol for ultrasonic cleaning for 3-5 minutes, taken out and air-dried, and then immersed in a 3% acetic acid solution for 10-15 seconds, then rinsed with clean water until neutral, and then immersed in a surface treatment agent for 30 minutes, taken out and naturally dried to obtain the final product.
[0032] The mixed gas A is composed of air, carbon dioxide and sulfur hexafluoride in a volume ratio of 50:50:3; the mixed gas B is composed of carbon dioxide and sulfur hexafluoride in a volume ratio of 97:3.
[0033] The homogenization treatment method is: using gradient setting temperature homogenization treatment, specifically, setting the temperature to 100°C and keeping warm for 30 minutes; setting the temperature to 200°C and keeping warm for 20 minutes; setting the temperature to 300°C and keeping warm for 20 minutes; setting the temperature to 390°C and keeping warm for 21 hours.
[0034] The aging treatment was performed at a temperature of 177±6°C, for a time of 6 hours, and at a heating rate of 5°C / min.
[0035] The surface treatment agent is composed of modified nano magnesium hydroxide slurry and silica sol in a volume ratio of 1:1; the mass fraction of the modified nano magnesium hydroxide slurry is 10%.
[0036] The modified magnesium hydroxide is prepared by the following method: a) preparing anhydrous ethanol and deionized water in a volume ratio of 9:1 to prepare an alcohol-water solvent, mixing N-phenyl-γ-aminopropyltrimethoxysilane coupling agent and the alcohol-water solvent in a volume ratio of 100:1, stirring and hydrolyzing with magnetic stirring for 1 hour to obtain a silane hydrolyzate; b) Nano magnesium hydroxide was weighed and prepared into a nano magnesium hydroxide slurry with a mass fraction of 10%. After ultrasonic dispersion treatment for 15 minutes, the slurry was heated to 90° C., and then the silane hydrolyzate obtained in step a) was slowly dripped into it under magnetic stirring. After the dripping was completed, the system was kept reacting for 45 minutes, and then the obtained white slurry was filtered to obtain a white filter cake, and then the filter cake was washed three times with deionized water and anhydrous ethanol respectively to obtain modified nano magnesium hydroxide.
[0037] The volume ratio of the nano magnesium hydroxide slurry to the silane hydrolyzate is 10:1; the nano magnesium hydroxide is flaky nano magnesium hydroxide, and its average particle size D50 is 500nm.
[0038] The silica sol has a nano-silicon dioxide content of 25%, a particle size of 70 nm, and a pH of 8.2.
[0039] Example 3 A low-cost high-strength flame-retardant magnesium alloy profile is made of the following raw materials in weight percentage: Al 10.8%, Sn 1.0%, Ca 1.2%, Zn 0.6%, Mn 0.12%, Si 0.3%, Sr 0.2%, and the balance Mg and inevitable impurities.
[0040] A method for preparing the above-mentioned low-cost, high-strength, flame-retardant magnesium alloy profile comprises the following steps: 1) Prepare raw materials: weigh the raw materials according to the mass percentage of each raw material in the magnesium alloy, wherein magnesium, aluminum, zinc, and tin are added in the form of pure magnesium ingots, aluminum ingots, zinc ingots, and tin ingots, calcium, strontium, and silicon are added in the form of magnesium-calcium alloy, magnesium-strontium alloy, and magnesium-silicon alloy, and manganese is manganese chloride; 2) Melting: First, the magnesium ingot is preheated, and the preheated magnesium ingot is placed in the furnace body for melting under the protection of mixed gas A. After the melting is complete, the preheated aluminum ingot, zinc ingot, tin ingot, magnesium calcium alloy, magnesium strontium alloy, magnesium silicon alloy and No. 2 flux, and manganese chloride are added thereto and continue to be mixed and smelted at 710-740°C under the protection of mixed gas B. After all are melted, a refining agent is added and refined for 10-15 minutes, and then degassing, slag removal and heat preservation treatment are carried out in sequence to obtain an alloy melt, and a covering agent is added. The melt is left to stand for 15-20 minutes, and the semi-continuous casting billet is obtained when the temperature reaches 670-690°C; 3) Homogenization treatment: homogenize the semi-continuous casting billet, then cool it to room temperature and turn the outer surface to the appropriate size; 4) Forming processing: The homogenized billet is preheated before extrusion, extruded and aged to obtain a flame-retardant magnesium alloy profile; 5) Surface treatment: The flame retardant magnesium alloy profile obtained in step 4) is immersed in anhydrous ethanol for ultrasonic cleaning for 3-5 minutes, taken out and air-dried, and then immersed in a 3% acetic acid solution for 10-15 seconds, then rinsed with clean water until neutral, and then immersed in a surface treatment agent for 30 minutes, taken out and naturally dried to obtain the final product.
[0041] The mixed gas A is composed of air, carbon dioxide and sulfur hexafluoride in a volume ratio of 50:50:3; the mixed gas B is composed of carbon dioxide and sulfur hexafluoride in a volume ratio of 97:3.
[0042] The homogenization treatment method is: using gradient setting temperature homogenization treatment, specifically, setting the temperature to 100°C and keeping warm for 30 minutes; setting the temperature to 200°C and keeping warm for 20 minutes; setting the temperature to 300°C and keeping warm for 20 minutes; setting the temperature to 390°C and keeping warm for 21 hours.
[0043] The aging treatment was performed at a temperature of 177±6°C, for a time of 6 hours, and at a heating rate of 5°C / min.
[0044] The surface treatment agent is composed of modified nano magnesium hydroxide slurry and silica sol in a volume ratio of 1:1; the mass fraction of the modified nano magnesium hydroxide slurry is 10%.
[0045] The modified magnesium hydroxide is prepared by the following method: a) preparing anhydrous ethanol and deionized water in a volume ratio of 9:1 to prepare an alcohol-water solvent, mixing N-phenyl-γ-aminopropyltrimethoxysilane coupling agent and the alcohol-water solvent in a volume ratio of 100:1, stirring and hydrolyzing with magnetic stirring for 1 hour to obtain a silane hydrolyzate; b) Nano magnesium hydroxide was weighed and prepared into a nano magnesium hydroxide slurry with a mass fraction of 10%. After ultrasonic dispersion treatment for 15 minutes, the slurry was heated to 90° C., and then the silane hydrolyzate obtained in step a) was slowly dripped into it under magnetic stirring. After the dripping was completed, the system was kept reacting for 45 minutes, and then the obtained white slurry was filtered to obtain a white filter cake, and then the filter cake was washed three times with deionized water and anhydrous ethanol respectively to obtain modified nano magnesium hydroxide.
[0046] The volume ratio of the nano magnesium hydroxide slurry to the silane hydrolyzate is 10:1; the nano magnesium hydroxide is flaky nano magnesium hydroxide, and its average particle size D50 is 500nm.
[0047] The silica sol has a nano-silicon dioxide content of 25%, a particle size of 80 nm, and a pH of 8.5.
[0048] Comparative Example 1 A low-cost high-strength flame-retardant magnesium alloy profile is made of the following raw materials in weight percentage: Al 10.8%, Sn 1.0%, Ca 1.2%, Zn 0.6%, Mn 0.12%, Si 0.3%, Sr 0.2%, and the balance Mg and inevitable impurities.
[0049] A method for preparing the above-mentioned low-cost, high-strength, flame-retardant magnesium alloy profile comprises the following steps: 1) Prepare raw materials: weigh the raw materials according to the mass percentage of each raw material in the magnesium alloy, wherein magnesium, aluminum, zinc, and tin are added in the form of pure magnesium ingots, aluminum ingots, zinc ingots, and tin ingots, calcium, strontium, and silicon are added in the form of magnesium-calcium alloy, magnesium-strontium alloy, and magnesium-silicon alloy, and manganese is manganese chloride; 2) Melting: First, the magnesium ingot is preheated, and the preheated magnesium ingot is placed in the furnace body for melting under the protection of mixed gas A. After the melting is complete, the preheated aluminum ingot, zinc ingot, tin ingot, magnesium calcium alloy, magnesium strontium alloy, magnesium silicon alloy and No. 2 flux, and manganese chloride are added thereto and continue to be mixed and smelted at 710-740°C under the protection of mixed gas B. After all are melted, a refining agent is added and refined for 10-15 minutes, and then degassing, slag removal and heat preservation treatment are carried out in sequence to obtain an alloy melt, and a covering agent is added. The melt is left to stand for 15-20 minutes, and the semi-continuous casting billet is obtained when the temperature reaches 670-690°C; 3) Homogenization treatment: homogenize the semi-continuous casting billet, then cool it to room temperature and turn the outer surface to the appropriate size; 4) Forming processing: The homogenized billet is preheated before extrusion, extruded and aged to obtain a flame-retardant magnesium alloy profile; 5) Surface treatment: The flame retardant magnesium alloy profile obtained in step 4) is immersed in anhydrous ethanol for ultrasonic cleaning for 3-5 minutes, taken out and air-dried, and then immersed in a 3% acetic acid solution for 10-15 seconds, then rinsed with clean water until neutral, and then immersed in a surface treatment agent for 30 minutes, taken out and naturally dried to obtain the final product.
[0050] The mixed gas A is composed of air, carbon dioxide and sulfur hexafluoride in a volume ratio of 50:50:3; the mixed gas B is composed of carbon dioxide and sulfur hexafluoride in a volume ratio of 97:3.
[0051] The homogenization treatment method is: using gradient setting temperature homogenization treatment, specifically, setting the temperature to 100°C and keeping warm for 30 minutes; setting the temperature to 200°C and keeping warm for 20 minutes; setting the temperature to 300°C and keeping warm for 20 minutes; setting the temperature to 390°C and keeping warm for 21 hours.
[0052] The aging treatment was performed at a temperature of 177±6°C, for a time of 6 hours, and at a heating rate of 5°C / min.
[0053] The surface treatment agent is composed of nano magnesium hydroxide slurry and silica sol in a volume ratio of 1:1; the nano magnesium hydroxide is flaky nano magnesium hydroxide with an average particle size D50 of 500 nm. The mass fraction of the nano magnesium hydroxide slurry is 10%.
[0054] The silica sol has a nano-silicon dioxide content of 25%, a particle size of 80 nm, and a pH of 8.5.
[0055] The raw material composition and preparation method of this comparative example are basically the same as those of Example 3, with the only difference being that the surface treatment agent used is a slurry made of commercially available nano magnesium hydroxide and silica sol in a volume ratio of 1:1.
[0056] Comparative Example 2 A low-cost high-strength flame-retardant magnesium alloy profile is made of the following raw materials in weight percentage: Al 10.8%, Sn 1.0%, Ca 1.2%, Zn 0.6%, Mn 0.12%, Si 0.3%, Sr 0.2%, and the balance Mg and inevitable impurities.
[0057] A method for preparing the above-mentioned low-cost, high-strength, flame-retardant magnesium alloy profile comprises the following steps: 1) Prepare raw materials: weigh the raw materials according to the mass percentage of each raw material in the magnesium alloy, wherein magnesium, aluminum, zinc, and tin are added in the form of pure magnesium ingots, aluminum ingots, zinc ingots, and tin ingots, calcium, strontium, and silicon are added in the form of magnesium-calcium alloy, magnesium-strontium alloy, and magnesium-silicon alloy, and manganese is manganese chloride; 2) Melting: First, the magnesium ingot is preheated, and the preheated magnesium ingot is placed in the furnace body for melting under the protection of mixed gas A. After the melting is complete, the preheated aluminum ingot, zinc ingot, tin ingot, magnesium calcium alloy, magnesium strontium alloy, magnesium silicon alloy and No. 2 flux, and manganese chloride are added thereto and continue to be mixed and smelted at 710-740°C under the protection of mixed gas B. After all are melted, a refining agent is added and refined for 10-15 minutes, and then degassing, slag removal and heat preservation treatment are carried out in sequence to obtain an alloy melt, and a covering agent is added. The melt is left to stand for 15-20 minutes, and the semi-continuous casting billet is obtained when the temperature reaches 670-690°C; 3) Homogenization treatment: homogenize the semi-continuous casting billet, then cool it to room temperature and turn the outer surface to the appropriate size; 4) Forming processing: The homogenized billet is preheated before extrusion, extruded and aged to obtain a flame-retardant magnesium alloy profile; 5) Surface treatment: The flame retardant magnesium alloy profile obtained in step 4) is immersed in anhydrous ethanol for ultrasonic cleaning for 3-5 minutes, taken out and air-dried, and then immersed in a 3% acetic acid solution for 10-15 seconds, then rinsed with clean water until neutral, and then immersed in a surface treatment agent for 30 minutes, taken out and naturally dried to obtain the final product.
[0058] The mixed gas A is composed of air, carbon dioxide and sulfur hexafluoride in a volume ratio of 50:50:3; the mixed gas B is composed of carbon dioxide and sulfur hexafluoride in a volume ratio of 97:3.
[0059] The homogenization treatment method is: using gradient setting temperature homogenization treatment, specifically, setting the temperature to 100°C and keeping warm for 30 minutes; setting the temperature to 200°C and keeping warm for 20 minutes; setting the temperature to 300°C and keeping warm for 20 minutes; setting the temperature to 390°C and keeping warm for 21 hours.
[0060] The aging treatment was performed at a temperature of 177±6°C, for a time of 6 hours, and at a heating rate of 5°C / min.
[0061] The surface treatment agent is silica sol, in which the content of nano-silicon dioxide is 25%, the particle size is 80nm, and the pH is 8.5.
[0062] The raw material composition and preparation method of this comparative example are basically the same as those of Example 3, with the only difference being that the surface treatment agent used is silica sol.
[0063] Comparative Example 3 A low-cost high-strength flame-retardant magnesium alloy profile is made of the following raw materials in weight percentage: Al 10.8%, Sn 1.0%, Ca 1.2%, Zn 0.6%, Mn 0.12%, Si 0.3%, Sr 0.2%, and the balance Mg and inevitable impurities.
[0064] A method for preparing the above-mentioned low-cost, high-strength, flame-retardant magnesium alloy profile comprises the following steps: 1) Prepare raw materials: weigh the raw materials according to the mass percentage of each raw material in the magnesium alloy, wherein magnesium, aluminum, zinc, and tin are added in the form of pure magnesium ingots, aluminum ingots, zinc ingots, and tin ingots, calcium, strontium, and silicon are added in the form of magnesium-calcium alloy, magnesium-strontium alloy, and magnesium-silicon alloy, and manganese is manganese chloride; 2) Melting: First, the magnesium ingot is preheated, and the preheated magnesium ingot is placed in the furnace body for melting under the protection of mixed gas A. After the melting is complete, the preheated aluminum ingot, zinc ingot, tin ingot, magnesium calcium alloy, magnesium strontium alloy, magnesium silicon alloy and No. 2 flux, and manganese chloride are added thereto and continue to be mixed and smelted at 710-740°C under the protection of mixed gas B. After all are melted, a refining agent is added and refined for 10-15 minutes, and then degassing, slag removal and heat preservation treatment are carried out in sequence to obtain an alloy melt, and a covering agent is added. The melt is left to stand for 15-20 minutes, and the semi-continuous casting billet is obtained when the temperature reaches 670-690°C; 3) Homogenization treatment: homogenize the semi-continuous casting billet, then cool it to room temperature and turn the outer surface to the appropriate size; 4) Forming processing: The homogenized billet is preheated before extrusion, extruded and aged to obtain a flame-retardant magnesium alloy profile; 5) Surface treatment: The flame retardant magnesium alloy profile obtained in step 4) is immersed in anhydrous ethanol for ultrasonic cleaning for 3-5 minutes, taken out and air-dried, and then immersed in a 3% acetic acid solution for 10-15 seconds, then rinsed with clean water until neutral, and then immersed in a surface treatment agent for 30 minutes, taken out and naturally dried to obtain the final product.
[0065] The mixed gas A is composed of air, carbon dioxide and sulfur hexafluoride in a volume ratio of 50:50:3; the mixed gas B is composed of carbon dioxide and sulfur hexafluoride in a volume ratio of 97:3.
[0066] The homogenization treatment method is: using gradient setting temperature homogenization treatment, specifically, setting the temperature to 100°C and keeping warm for 30 minutes; setting the temperature to 200°C and keeping warm for 20 minutes; setting the temperature to 300°C and keeping warm for 20 minutes; setting the temperature to 390°C and keeping warm for 21 hours.
[0067] The aging treatment was performed at a temperature of 177±6°C, for a time of 6 hours, and at a heating rate of 5°C / min.
[0068] The surface treatment agent is composed of modified nano magnesium hydroxide slurry and silica sol in a volume ratio of 0.5:1; the mass fraction of the modified nano magnesium hydroxide slurry is 10%.
[0069] The modified magnesium hydroxide is prepared by the following method: a) preparing anhydrous ethanol and deionized water in a volume ratio of 9:1 to prepare an alcohol-water solvent, mixing N-phenyl-γ-aminopropyltrimethoxysilane coupling agent and the alcohol-water solvent in a volume ratio of 100:1, stirring and hydrolyzing with magnetic stirring for 1 hour to obtain a silane hydrolyzate; b) Nano magnesium hydroxide was weighed and prepared into a nano magnesium hydroxide slurry with a mass fraction of 10%. After ultrasonic dispersion treatment for 15 minutes, the slurry was heated to 90° C., and then the silane hydrolyzate obtained in step a) was slowly dripped into it under magnetic stirring. After the dripping was completed, the system was kept reacting for 45 minutes, and then the obtained white slurry was filtered to obtain a white filter cake, and then the filter cake was washed three times with deionized water and anhydrous ethanol respectively to obtain modified nano magnesium hydroxide.
[0070] The volume ratio of the nano magnesium hydroxide slurry to the silane hydrolyzate is 10:1; the nano magnesium hydroxide is flaky nano magnesium hydroxide, and its average particle size D50 is 500nm.
[0071] The silica sol has a nano-silicon dioxide content of 25%, a particle size of 80 nm, and a pH of 8.5.
[0072] The raw material composition and preparation method of this comparative example are basically the same as those of Example 3, except that the surface treatment agent used is a modified nano-magnesium hydroxide slurry and a silica sol in a volume ratio of 0.5:1.
[0073] Comparative Example 4 A low-cost high-strength flame-retardant magnesium alloy profile is made of the following raw materials in weight percentage: Al 10.8%, Sn 1.0%, Ca 1.2%, Zn 0.6%, Mn 0.12%, Si 0.3%, Sr 0.2%, and the balance Mg and inevitable impurities.
[0074] A method for preparing the above-mentioned low-cost, high-strength, flame-retardant magnesium alloy profile comprises the following steps: 1) Prepare raw materials: weigh the raw materials according to the mass percentage of each raw material in the magnesium alloy, wherein magnesium, aluminum, zinc, and tin are added in the form of pure magnesium ingots, aluminum ingots, zinc ingots, and tin ingots, calcium, strontium, and silicon are added in the form of magnesium-calcium alloy, magnesium-strontium alloy, and magnesium-silicon alloy, and manganese is manganese chloride; 2) Melting: First, the magnesium ingot is preheated, and the preheated magnesium ingot is placed in the furnace body for melting under the protection of mixed gas A. After the melting is complete, the preheated aluminum ingot, zinc ingot, tin ingot, magnesium calcium alloy, magnesium strontium alloy, magnesium silicon alloy and No. 2 flux, and manganese chloride are added thereto and continue to be mixed and smelted at 710-740°C under the protection of mixed gas B. After all are melted, a refining agent is added and refined for 10-15 minutes, and then degassing, slag removal and heat preservation treatment are carried out in sequence to obtain an alloy melt, and a covering agent is added. The melt is left to stand for 15-20 minutes, and the semi-continuous casting billet is obtained when the temperature reaches 670-690°C; 3) Homogenization treatment: homogenize the semi-continuous casting billet, then cool it to room temperature and turn the outer surface to the appropriate size; 4) Forming processing: The homogenized billet is preheated before extrusion, extruded and aged to obtain a flame-retardant magnesium alloy profile; 5) Surface treatment: The flame retardant magnesium alloy profile obtained in step 4) is immersed in anhydrous ethanol for ultrasonic cleaning for 3-5 minutes, taken out and air-dried, and then immersed in a 3% acetic acid solution for 10-15 seconds, then rinsed with clean water until neutral, and then immersed in a surface treatment agent for 30 minutes, taken out and naturally dried to obtain the final product.
[0075] The mixed gas A is composed of air, carbon dioxide and sulfur hexafluoride in a volume ratio of 50:50:3; the mixed gas B is composed of carbon dioxide and sulfur hexafluoride in a volume ratio of 97:3.
[0076] The homogenization treatment method is: using gradient setting temperature homogenization treatment, specifically, setting the temperature to 100°C and keeping warm for 30 minutes; setting the temperature to 200°C and keeping warm for 20 minutes; setting the temperature to 300°C and keeping warm for 20 minutes; setting the temperature to 390°C and keeping warm for 21 hours.
[0077] The aging treatment was performed at a temperature of 177±6°C, for a time of 6 hours, and at a heating rate of 5°C / min.
[0078] The surface treatment agent is composed of modified nano magnesium hydroxide slurry and silica sol in a volume ratio of 0.8:1; the mass fraction of the modified nano magnesium hydroxide slurry is 10%.
[0079] The modified magnesium hydroxide is prepared by the following method: a) preparing anhydrous ethanol and deionized water in a volume ratio of 9:1 to prepare an alcohol-water solvent, mixing N-phenyl-γ-aminopropyltrimethoxysilane coupling agent and the alcohol-water solvent in a volume ratio of 100:1, stirring and hydrolyzing with magnetic stirring for 1 hour to obtain a silane hydrolyzate; b) Nano magnesium hydroxide was weighed and prepared into a nano magnesium hydroxide slurry with a mass fraction of 10%. After ultrasonic dispersion treatment for 15 minutes, the slurry was heated to 90° C., and then the silane hydrolyzate obtained in step a) was slowly dripped into it under magnetic stirring. After the dripping was completed, the system was kept reacting for 45 minutes, and then the obtained white slurry was filtered to obtain a white filter cake, and then the filter cake was washed three times with deionized water and anhydrous ethanol respectively to obtain modified nano magnesium hydroxide.
[0080] The volume ratio of the nano magnesium hydroxide slurry to the silane hydrolyzate is 10:1; the nano magnesium hydroxide is flaky nano magnesium hydroxide, and its average particle size D50 is 500nm.
[0081] The silica sol has a nano-silicon dioxide content of 25%, a particle size of 80 nm, and a pH of 8.5.
[0082] The surface treatment agent is composed of modified nano magnesium hydroxide slurry and silica sol in a volume ratio of 0.8:1; the mass fraction of the modified nano magnesium hydroxide slurry is 10%.
[0083] The raw material composition and preparation method of this comparative example are basically the same as those of Example 3, except that the surface treatment agent used is a modified nano-magnesium hydroxide slurry and a silica sol in a volume ratio of 0.8:1.
[0084] Comparative Example 5 A low-cost high-strength flame-retardant magnesium alloy profile is made of the following raw materials in weight percentage: Al 10.8%, Sn 1.0%, Ca 1.2%, Zn 0.6%, Mn 0.12%, Si 0.3%, Sr 0.2%, and the balance Mg and inevitable impurities.
[0085] A method for preparing the above-mentioned low-cost, high-strength, flame-retardant magnesium alloy profile comprises the following steps: 1) Prepare raw materials: weigh the raw materials according to the mass percentage of each raw material in the magnesium alloy, wherein magnesium, aluminum, zinc, and tin are added in the form of pure magnesium ingots, aluminum ingots, zinc ingots, and tin ingots, calcium, strontium, and silicon are added in the form of magnesium-calcium alloy, magnesium-strontium alloy, and magnesium-silicon alloy, and manganese is manganese chloride; 2) Melting: First, the magnesium ingot is preheated, and the preheated magnesium ingot is placed in the furnace body for melting under the protection of mixed gas A. After the melting is complete, the preheated aluminum ingot, zinc ingot, tin ingot, magnesium calcium alloy, magnesium strontium alloy, magnesium silicon alloy and No. 2 flux, and manganese chloride are added thereto and continue to be mixed and smelted at 710-740°C under the protection of mixed gas B. After all are melted, a refining agent is added and refined for 10-15 minutes, and then degassing, slag removal and heat preservation treatment are carried out in sequence to obtain an alloy melt, and a covering agent is added. The melt is left to stand for 15-20 minutes, and the semi-continuous casting billet is obtained when the temperature reaches 670-690°C; 3) Homogenization treatment: homogenize the semi-continuous casting billet, then cool it to room temperature and turn the outer surface to the appropriate size; 4) Forming processing: The homogenized billet is preheated before extrusion, extruded and aged to obtain a flame-retardant magnesium alloy profile; 5) Surface treatment: The flame retardant magnesium alloy profile obtained in step 4) is immersed in anhydrous ethanol for ultrasonic cleaning for 3-5 minutes, taken out and air-dried, and then immersed in a 3% acetic acid solution for 10-15 seconds, then rinsed with clean water until neutral, and then immersed in a surface treatment agent for 30 minutes, taken out and naturally dried to obtain the final product.
[0086] The mixed gas A is composed of air, carbon dioxide and sulfur hexafluoride in a volume ratio of 50:50:3; the mixed gas B is composed of carbon dioxide and sulfur hexafluoride in a volume ratio of 97:3.
[0087] The homogenization treatment method is: using gradient setting temperature homogenization treatment, specifically, setting the temperature to 100°C and keeping warm for 30 minutes; setting the temperature to 200°C and keeping warm for 20 minutes; setting the temperature to 300°C and keeping warm for 20 minutes; setting the temperature to 390°C and keeping warm for 21 hours.
[0088] The aging treatment was performed at a temperature of 177±6°C, for a time of 6 hours, and at a heating rate of 5°C / min.
[0089] The surface treatment agent is composed of modified nano magnesium hydroxide slurry and silica sol in a volume ratio of 1.5:1; the mass fraction of the modified nano magnesium hydroxide slurry is 10%.
[0090] The modified magnesium hydroxide is prepared by the following method: a) preparing anhydrous ethanol and deionized water in a volume ratio of 9:1 to prepare an alcohol-water solvent, mixing N-phenyl-γ-aminopropyltrimethoxysilane coupling agent and the alcohol-water solvent in a volume ratio of 100:1, stirring and hydrolyzing with magnetic stirring for 1 hour to obtain a silane hydrolyzate; b) Nano magnesium hydroxide was weighed and prepared into a nano magnesium hydroxide slurry with a mass fraction of 10%. After ultrasonic dispersion treatment for 15 minutes, the slurry was heated to 90° C., and then the silane hydrolyzate obtained in step a) was slowly dripped into it under magnetic stirring. After the dripping was completed, the system was kept reacting for 45 minutes, and then the obtained white slurry was filtered to obtain a white filter cake, and then the filter cake was washed three times with deionized water and anhydrous ethanol respectively to obtain modified nano magnesium hydroxide.
[0091] The volume ratio of the nano magnesium hydroxide slurry to the silane hydrolyzate is 10:1; the nano magnesium hydroxide is flaky nano magnesium hydroxide, and its average particle size D50 is 500nm.
[0092] The silica sol has a nano-silicon dioxide content of 25%, a particle size of 80 nm, and a pH of 8.5.
[0093] The surface treatment agent is composed of modified nano magnesium hydroxide slurry and silica sol in a volume ratio of 1.5:1; the mass fraction of the modified nano magnesium hydroxide slurry is 10%.
[0094] The raw material composition and preparation method of this comparative example are basically the same as those of Example 3, except that the surface treatment agent used is a modified nano-magnesium hydroxide slurry and a silica sol in a volume ratio of 1.5:1.
[0095] Comparative Example 6 A low-cost high-strength flame-retardant magnesium alloy profile is made of the following raw materials in weight percentage: Al 10.8%, Sn 1.0%, Ca 1.2%, Zn 0.6%, Mn 0.12%, Si 0.3%, Sr 0.2%, and the balance Mg and inevitable impurities.
[0096] A method for preparing the above-mentioned low-cost, high-strength, flame-retardant magnesium alloy profile comprises the following steps: 1) Prepare raw materials: weigh the raw materials according to the mass percentage of each raw material in the magnesium alloy, wherein magnesium, aluminum, zinc, and tin are added in the form of pure magnesium ingots, aluminum ingots, zinc ingots, and tin ingots, calcium, strontium, and silicon are added in the form of magnesium-calcium alloy, magnesium-strontium alloy, and magnesium-silicon alloy, and manganese is manganese chloride; 2) Melting: First, the magnesium ingot is preheated, and the preheated magnesium ingot is placed in the furnace body for melting under the protection of mixed gas A. After the melting is complete, the preheated aluminum ingot, zinc ingot, tin ingot, magnesium calcium alloy, magnesium strontium alloy, magnesium silicon alloy and No. 2 flux, and manganese chloride are added thereto and continue to be mixed and smelted at 710-740°C under the protection of mixed gas B. After all are melted, a refining agent is added and refined for 10-15 minutes, and then degassing, slag removal and heat preservation treatment are carried out in sequence to obtain an alloy melt, and a covering agent is added. The melt is left to stand for 15-20 minutes, and the semi-continuous casting billet is obtained when the temperature reaches 670-690°C; 3) Homogenization treatment: homogenize the semi-continuous casting billet, then cool it to room temperature and turn the outer surface to the appropriate size; 4) Forming processing: The homogenized billet is preheated before extrusion, extruded and aged to obtain a flame-retardant magnesium alloy profile; 5) Surface treatment: The flame retardant magnesium alloy profile obtained in step 4) is immersed in anhydrous ethanol for ultrasonic cleaning for 3-5 minutes, taken out and air-dried, and then immersed in a 3% acetic acid solution for 10-15 seconds, then rinsed with clean water until neutral, and then immersed in a surface treatment agent for 30 minutes, taken out and naturally dried to obtain the final product.
[0097] The mixed gas A is composed of air, carbon dioxide and sulfur hexafluoride in a volume ratio of 50:50:3; the mixed gas B is composed of carbon dioxide and sulfur hexafluoride in a volume ratio of 97:3.
[0098] The homogenization treatment method is: using gradient setting temperature homogenization treatment, specifically, setting the temperature to 100°C and keeping warm for 30 minutes; setting the temperature to 200°C and keeping warm for 20 minutes; setting the temperature to 300°C and keeping warm for 20 minutes; setting the temperature to 390°C and keeping warm for 21 hours.
[0099] The aging treatment was performed at a temperature of 177±6°C, for a time of 6 hours, and at a heating rate of 5°C / min.
[0100] The surface treatment agent is composed of modified nano magnesium hydroxide slurry and silica sol in a volume ratio of 2:1; the mass fraction of the modified nano magnesium hydroxide slurry is 10%.
[0101] The modified magnesium hydroxide is prepared by the following method: a) preparing anhydrous ethanol and deionized water in a volume ratio of 9:1 to prepare an alcohol-water solvent, mixing N-phenyl-γ-aminopropyltrimethoxysilane coupling agent and the alcohol-water solvent in a volume ratio of 100:1, stirring and hydrolyzing with magnetic stirring for 1 hour to obtain a silane hydrolyzate; b) Nano magnesium hydroxide was weighed and prepared into a nano magnesium hydroxide slurry with a mass fraction of 10%. After ultrasonic dispersion treatment for 15 minutes, the slurry was heated to 90° C., and then the silane hydrolyzate obtained in step a) was slowly dripped into it under magnetic stirring. After the dripping was completed, the system was kept reacting for 45 minutes, and then the obtained white slurry was filtered to obtain a white filter cake, and then the filter cake was washed three times with deionized water and anhydrous ethanol respectively to obtain modified nano magnesium hydroxide.
[0102] The volume ratio of the nano magnesium hydroxide slurry to the silane hydrolyzate is 10:1; the nano magnesium hydroxide is flaky nano magnesium hydroxide, and its average particle size D50 is 500nm.
[0103] The silica sol has a nano-silicon dioxide content of 25%, a particle size of 80 nm, and a pH of 8.5.
[0104] The surface treatment agent is composed of modified nano magnesium hydroxide slurry and silica sol in a volume ratio of 2:1; the mass fraction of the modified nano magnesium hydroxide slurry is 10%.
[0105] The raw material composition and preparation method of this comparative example are basically the same as those of Example 3, except that the surface treatment agent used is a modified nano-magnesium hydroxide slurry and a silica sol in a volume ratio of 2:1.
[0106] Comparative Example 7 A low-cost high-strength flame-retardant magnesium alloy profile is made of the following raw materials in weight percentage: Al 10.8%, Sn 1.0%, Ca 1.2%, Zn 0.6%, Mn 0.12%, Si 0.3%, Sr 0.2%, and the balance Mg and inevitable impurities.
[0107] A method for preparing the above-mentioned low-cost, high-strength, flame-retardant magnesium alloy profile comprises the following steps: 1) Prepare raw materials: weigh the raw materials according to the mass percentage of each raw material in the magnesium alloy, wherein magnesium, aluminum, zinc, and tin are added in the form of pure magnesium ingots, aluminum ingots, zinc ingots, and tin ingots, calcium, strontium, and silicon are added in the form of magnesium-calcium alloy, magnesium-strontium alloy, and magnesium-silicon alloy, and manganese is manganese chloride; 2) Melting: First, the magnesium ingot is preheated, and the preheated magnesium ingot is placed in the furnace body for melting under the protection of mixed gas A. After the melting is complete, the preheated aluminum ingot, zinc ingot, tin ingot, magnesium calcium alloy, magnesium strontium alloy, magnesium silicon alloy and No. 2 flux, and manganese chloride are added thereto and continue to be mixed and smelted at 710-740°C under the protection of mixed gas B. After all are melted, a refining agent is added and refined for 10-15 minutes, and then degassing, slag removal and heat preservation treatment are carried out in sequence to obtain an alloy melt, and a covering agent is added. The melt is left to stand for 15-20 minutes, and the semi-continuous casting billet is obtained when the temperature reaches 670-690°C; 3) Homogenization treatment: homogenize the semi-continuous casting billet, then cool it to room temperature and turn the outer surface to the appropriate size; 4) Forming processing: The homogenized billet is preheated before extrusion, extruded and aged to obtain the final product, flame-retardant magnesium alloy profile.
[0108] The mixed gas A is composed of air, carbon dioxide and sulfur hexafluoride in a volume ratio of 50:50:3; the mixed gas B is composed of carbon dioxide and sulfur hexafluoride in a volume ratio of 97:3.
[0109] The homogenization treatment method is: using gradient setting temperature homogenization treatment, specifically, setting the temperature to 100°C and keeping warm for 30 minutes; setting the temperature to 200°C and keeping warm for 20 minutes; setting the temperature to 300°C and keeping warm for 20 minutes; setting the temperature to 390°C and keeping warm for 21 hours.
[0110] The aging treatment was performed at a temperature of 177±6°C, for a time of 6 hours, and at a heating rate of 5°C / min.
[0111] The raw material composition and preparation method of this comparative example are basically the same as those of Example 3, except that there is no step 5) of using a surface treatment agent for treatment.
[0112] Performance Testing The surface morphology of the flame-retardant magnesium alloy sheet prepared in Example 3 of the present invention was observed on a S-4800 scanning electron microscope at an operating voltage of 20 kV. Figure 1 shown.
[0113] The low-cost, high-strength flame-retardant magnesium alloy profiles prepared in Examples 1-3 and Comparative Examples 1-7 were respectively subjected to ignition point tests and mechanical property tests (using the national standard GB / T 228.1-2021), and the test results are shown in Table 1.
[0114] Table 1 Performance test results It can be seen from the data in Table 1 above that the low-cost high-strength flame-retardant magnesium alloy prepared by the present invention has a tensile strength of more than 360 MPa, a yield strength of more than 310 MPa, and an average elongation of 18.1. The prepared magnesium alloy profile is subjected to a combustion test at 1500°C, and only melts but does not burn within 20 minutes ( Figure 2 ), and no rare earth elements are added in the alloy preparation, and the production cost is low. Therefore, the low-cost and high-strength flame-retardant magnesium alloy prepared by the present invention has good market application prospects. Comparing Comparative Example 1 with Examples 1-3, it can be seen that the ignition point is significantly reduced. This is because the unmodified nano-magnesium hydroxide is seriously agglomerated, has poor dispersibility on the surface of the alloy matrix, and has poor interface bonding force, and cannot form a good flame retardant effect; the data results of Comparative Example 2 show that after the alloy surface is treated with a single silica sol, the mechanical properties are improved but the ignition point is not significantly improved; from the results of Comparative Examples 3-6, it can be seen that after the modified nano-magnesium hydroxide is used in combination with silica sol, a good flame retardant effect can only be achieved within an appropriate range. When the content of modified nano-magnesium hydroxide is too high, due to the strong agglomeration between nano-magnesium hydroxide grains, it is easy to agglomerate to form a larger secondary particle size after excessive use, which destroys the formation of a more dense and uniform micro-nano layer on the alloy surface, thereby causing the flame retardant effect to deteriorate, the ignition point to decrease, and the mechanical properties to decrease accordingly. In particular, the mechanical properties of excessive nano-magnesium hydroxide are even worse than those of Comparative Example 7.
[0115] It should be noted that the above embodiments are only partial embodiments of the preferred methods of implementing the present invention, rather than all embodiments. Obviously, based on the above embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
Claims
1. A low-cost, high-strength, flame-retardant magnesium alloy profile, characterized in that: It is made of the following raw materials in weight percentage: Al 10.2-11.0%, Sn 0.9-1.1%, Ca 0.75-1.3%, Zn 0.4-0.8%, Mn 0.1-0.5%, Si 0.2-0.4%, Sr0.1-0.3%, balance Mg and inevitable impurities.
2. A method for preparing the low-cost, high-strength, flame-retardant magnesium alloy profile according to claim 1, characterized in that: It includes the following steps: 1) Prepare raw materials: weigh the raw materials according to the mass percentage of each raw material in the magnesium alloy, wherein magnesium, aluminum, zinc, and tin are added in the form of pure magnesium ingots, aluminum ingots, zinc ingots, and tin ingots, calcium, strontium, and silicon are added in the form of magnesium-calcium alloy, magnesium-strontium alloy, and magnesium-silicon alloy, and manganese is manganese chloride; 2) Melting: First, the magnesium ingot is preheated, and the preheated magnesium ingot is placed in the furnace body for melting under the protection of mixed gas A. After the melting is complete, the preheated aluminum ingot, zinc ingot, tin ingot, magnesium calcium alloy, magnesium strontium alloy, magnesium silicon alloy and No. 2 flux, and manganese chloride are added thereto and continue to be mixed and smelted at 710-740°C under the protection of mixed gas B. After all are melted, a refining agent is added and refined for 10-15 minutes, and then degassing, slag removal and heat preservation treatment are carried out in sequence to obtain an alloy melt, and a covering agent is added. The melt is left to stand for 15-20 minutes, and the semi-continuous casting billet is obtained when the temperature reaches 670-690°C; 3) Homogenization treatment: homogenize the semi-continuous casting billet, then cool it to room temperature and turn the outer surface to the appropriate size; 4) Forming processing: The homogenized billet is preheated before extrusion, extruded, and aging treated to obtain a flame-retardant magnesium alloy profile; 5) Surface treatment: The flame retardant magnesium alloy profile obtained in step 4) is immersed in anhydrous ethanol for ultrasonic cleaning for 3-5 minutes, taken out and air-dried, and then immersed in a 3% acetic acid solution for 10-15 seconds, then rinsed with clean water until neutral, and then immersed in a surface treatment agent for 30 minutes, taken out and naturally dried to obtain the final product.
3. The method for preparing a low-cost, high-strength, flame-retardant magnesium alloy profile according to claim 2, characterized in that: The mixed gas A is composed of air, carbon dioxide and sulfur hexafluoride in a volume ratio of 50:50:3; the mixed gas B is composed of carbon dioxide and sulfur hexafluoride in a volume ratio of 97:
3.
4. The method for preparing a low-cost, high-strength, flame-retardant magnesium alloy profile according to claim 2, characterized in that: The homogenization treatment method is: using gradient setting temperature homogenization treatment, specifically, setting the temperature to 100°C and keeping warm for 30 minutes; setting the temperature to 200°C and keeping warm for 20 minutes; setting the temperature to 300°C and keeping warm for 20 minutes; setting the temperature to 390°C and keeping warm for 21 hours.
5. The method for preparing a low-cost, high-strength, flame-retardant magnesium alloy profile according to claim 2, characterized in that: The aging treatment was performed at a temperature of 177±6°C, for a time of 6 hours, and at a heating rate of 5°C / min.
6. The method for preparing a low-cost, high-strength, flame-retardant magnesium alloy profile according to claim 2, characterized in that: The surface treatment agent is composed of modified nano magnesium hydroxide slurry and silica sol in a volume ratio of 1:1; the mass fraction of the modified nano magnesium hydroxide slurry is 10%.
7. The method for preparing a low-cost, high-strength, flame-retardant magnesium alloy profile according to claim 6, characterized in that: The modified magnesium hydroxide is prepared by the following method: a) preparing anhydrous ethanol and deionized water in a volume ratio of 9:1 to prepare an alcohol-water solvent, mixing N-phenyl-γ-aminopropyltrimethoxysilane coupling agent and the alcohol-water solvent in a volume ratio of 100:1, stirring and hydrolyzing with magnetic stirring for 1 hour to obtain a silane hydrolyzate; b) Nano magnesium hydroxide was weighed and prepared into a nano magnesium hydroxide slurry with a mass fraction of 10%. After ultrasonic dispersion treatment for 15 minutes, the slurry was heated to 90° C., and then the silane hydrolyzate obtained in step a) was slowly dripped into it under magnetic stirring. After the dripping was completed, the system was kept reacting for 45 minutes, and then the obtained white slurry was filtered to obtain a white filter cake, and then the filter cake was washed three times with deionized water and anhydrous ethanol respectively to obtain modified nano magnesium hydroxide.
8. The method for preparing a low-cost, high-strength, flame-retardant magnesium alloy profile according to claim 7, characterized in that: The volume ratio of the nano magnesium hydroxide slurry to the silane hydrolyzate is 10:1; the nano magnesium hydroxide is flaky nano magnesium hydroxide, and its average particle size D50 is 500nm.
9. The method for preparing a low-cost, high-strength, flame-retardant magnesium alloy profile according to claim 6, characterized in that: The silica sol has a nano-silicon dioxide content of 25%, a particle size of 50-80 nm, and a pH of 8-8.5.
Citation Information
Cited By
Preparation method of ultra-fine grain high-toughness magnesium-based composite material
CN121450972A
Preparation method of ultrafine-grain high-strength and high-toughness magnesium-based composite material
CN121450972B
High-strength high-toughness low-cost flame-retardant magnesium alloy and preparation method thereof
CN122542892A
